Terence Fletcher's Strategy to Achieve Success in Whiplash (2014): A Machiavelli’s Perspective - Shafa Orland Ivandito; Sumayah (Universitas Veteran Bangun Nusantara, 2025)
This study analyzes Terence Fletcher's leadership strategy in Whiplash (2014) through the lens of Niccolò Machiavelli’s theory of power. Fletcher’s extreme methods manipulation, intimidation, and psychological pressure align with Machiavellian principles, particularly the idea that the ends justify the means. While previous studies have explored Fletcher’s psychological impact on students, they have not connected his methods to Machiavellian leadership. This research addresses this gap by examining Fletcher’s use of Machiavellian concepts such as virtù (personal ability) and fortuna (luck), and how they influence Andrew Neiman’s development as a musician. A qualitative analysis of key scenes in the film shows that Fletcher’s tactics, though ethically questionable, effectively push students beyond their limits, demonstrating that success in high-pressure environments often requires sacrifice and resilience. However, the study also highlights the emotional cost of such extreme methods. This research contributes to the understanding of Machiavellian leadership in competitive fields, suggesting that while extreme tactics may lead to success, they come with significant ethical and psychological consequences.